(untitled) (Al-Farooq Journal of Sciences, 2026)
This research provides a comprehensive study of the concept of human development amidst the rapid technological transformations that characterize the current era. It aims to analyze the opportunities offered by modern technology while simultaneously exploring the challenges and obstacles hindering this development, with a particular focus on the Libyan context. The central research problem is posed as a question of the nature of human development in the age of technology, considering both the available opportunities and existing challenges. To achieve this, the research seeks to clarify the comprehensive concept of human development, distinguishing it from limited, traditional development concepts. It also aims to define the role of technology as a fundamental driver of social change, identify the factors that either promote or impede development, and offer a scientific vision for overcoming challenges and maximizing opportunities. Methodologically, the research employs a descriptive-analytical approach, which includes a precise description of phenomena and problems and the identification of their causes. Within its conceptual and theoretical framework, the research defines development as a comprehensive and purposeful process of change that seeks to move society to a better state. Human development is defined as the harnessing of all resources to cultivate human innovative and inventive capabilities in order to achieve happiness, well-being, and complete freedom. Technology is viewed as a product of the evolution of human thought and as a set of processes geared towards social change. The research distinguishes between opportunities—favorable situations requiring intelligent and conscious utilization to achieve developmental progress—and challenges—obstacles to achieving development goals. These challenges include political and security instability, administrative and financial corruption, weak education and health systems, disguised unemployment, and cultural challenges such as resistance to change and dependency. The research reviewed previous studies by Dr. Mahmoud Abu Shneif and Dr. Ali Al-Hawwat, emphasizing the importance of addressing this topic within the Libyan context and the existing academic interest in it. The research concluded with several key findings, affirming that human development is the essence of progress and the eradication of ignorance and backwardness, and that it plays a crucial role in developing the capabilities and skills of individuals and societies. The findings also highlighted the paramount importance of raising social awareness about the concept of human development and the role of technology in our changing world, stressing the need to understand available opportunities and how to effectively utilize them, as well as to identify the obstacles. The study revealed that Libya, despite its natural resources and strategic location, faces significant challenges hindering human development, such as the absence of effective leadership and political division.